Pelatihan Manajemen Keuangan Bagi Umkm Kota Palangka Raya dan Pengelolaan Usahanya - Dicky Perwira Ompusunggu; Ditya Sriwahyni Sinurat (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research is expected to contribute to the development of MSMEs in the city of Palangka Raya, as well as to inspire MSMEs in Indonesia to manage their business finances well. This research uses a qualitative method with a descriptive approach, aiming to describe phenomena or events that occur in detail and comprehensively. In this study, data was collected using observational sources, namely direct observation of MSMEs participating in financial management training in Palangka Raya and running their businesses after the training. Financial management for MSMEs in Palangka Raya City, it can be concluded that MSME actors need more time to record their cash flow and need to improve their understanding of how to calculate profits accurately. This non-profit program presents financial management problems faced by MSMEs in Palangkaraya. Difficulty tracking cash flow, undercapitalization, mispriced, high bills, a mix of personal and corporate finances, and more.